2018
DOI: 10.33476/bibliotech.v3i2.914
|View full text |Cite
|
Sign up to set email alerts
|

EVALUASI PEMANFAATAN SISTEM INFORMASI KASUS DENGAN MODEL INFORMATION SYSTEM SUCCESS DELONE & MCLEAN DI LEMBAGA BANTUAN HUKUM JAKARTA

Abstract: Saat ini LBH Jakarta telah mengimplementasikan satu aplikasi yang memiliki peran penting dalam menangani pekerjaan-pekerjaan bantuan hukum. Model information system success Delone McLean digunakan untuk menganalisis Sistem Informasi Kasus (SIK) LBH. Terdapat enam variabel yang akan diuji dari yaitu, Information Quality, System Quality, Service Quality, Intention to Use/Use, User Satisfaction, dan Net Benefits. Hipotesis yang diajukan adalah, 1) Information Quality mempunyai pengaruh positif terhadap Intention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…It seems very clear that Fcount = 106,534 is greater than Ftable = 3.04, so it can be concluded that service quality is very influential on user satisfaction. This research is in line [14], showing that there is an influence between service quality on user satisfaction.…”
supporting
confidence: 63%
“…It seems very clear that Fcount = 106,534 is greater than Ftable = 3.04, so it can be concluded that service quality is very influential on user satisfaction. This research is in line [14], showing that there is an influence between service quality on user satisfaction.…”
supporting
confidence: 63%